Cultural Heritage of Culinary Specialties of Cirebon, West Java (Literature Review) - Ari Wibowo, Toni; Setiawan, Agung (Jurnal Toursci, 2024)
Various topics can be covered in research on traditional Cirebon cuisine, from its origins and history to the materials and cooking techniques employed to the significance of these dishes in Cirebon culture and daily life. These are some crucial areas that conventional Cirebon food research may concentrate on. The Origins and History of Jamblang Rice: This rice comes from Jamblang Village in Cirebon and is wrapped in teak leaves and served with various side dishes. Empal Gentong: A goulash-like dish made of beef cooked with traditional spices in a barrel (a clay container). White rice, teak leaves, and side dishes, including tempeh, jerky, tofu, and fried chili sauce, are used to make gambling rice. Lemongrass, turmeric, ginger, onion, garlic, coriander, cumin, bay leaf, and coconut milk are ingredients of empal gentong. Jamblang rice is a popular dish among travelers and is typically offered during important events and festivities. Empal Gentong: This meal is typically served at family gatherings and neighborhood festivals and can be obtained at food stands specializing in empal gentong. The Economic and Tourism Impact of Jamblang and Empal Gentong Rice: These two delicacies are not only the gastronomic highlights of Cirebon, but they also have a major impact on the local economy by drawing tourists. Contemporary Affects and Modifications Variations and modifications: These two dishes have undergone several modern modifications. For instance, the recipes for empal gentong and jamblang rice have been updated to suit modern preferences. Nutrition and Health Study Nutrition Analysis: Look at the nutritional value of empal gentong and jamblang rice and any possible health hazards. These meals' economic and tourism potential can be highlighted through research on Cirebon's traditional gastronomy, which can offer significant insight into the region's rich and diversified culinary heritage through this holistic approach.